Petrografia, geoquímica, química mineral e isótopos de S das mineralizações de Cu-Ni do Complexo Gabroico Canindé, Sistema Orogênico Sergipano - Damasceno, Fábio Bezerra (2019)
The Canindé Gabroico Complex (CGC) is an ultramographic body, that features Cu-Ni mineralizations, located in northeastern Brazil. With about 240 km2, the CGC is intrusive in metavulcansedimentary rocks of the Canindé Domain (DC), in the Sergipano Orogenic System. Their placement occurred during a distensional intracontinental event at 690 ± 16 Ma. It is constituted by a diversity of gabbroic rocks that have as main minerals plagioclase, amphibole and pyroxene, as accessrory minerals are observed oxides and sulfides, as well as a secondary mineralogical assembly. The mineralochemical results allow the identification of several Fe-Zn-Cu-Ni sulphides, where Cu-Ni mineralization occurs represented by chalcopyrite (FeCuS2) and pentlandite ((Fe, Ni)9S8), which occurs widespread in the gabbros. The obtained data determine the primary Cu-Ni sulphides that present their altered edges for spionkopite (Cu39S28) and violarite (FeNi2S4), resulting from a oxidation process by a hydrothermal fluid, in a postmagmatic event. As geochemical analyzes indicated that the rocks are basic and ultrabasic, they vary from gabbro to gabbro-peridotitic, with oxide behavior of fractional crystallization processes. An isotopic composition of sulfur are between 1.3 ‰ < δ34S < 2.7 ‰, showing a nonmagmatic S source, associating a δ34S with geological context and field data, it was possible propose which improved in S related to crustal contamination by assimilation of black shales from the DC country rocks. Our results allowed us to propose a metallogenic model for these occurrences, where we classify these mineralizations as magmatic with sulfur-added by crustal contamination, presenting a subsequent Cu-Ni enrichment associated with the remobilization of elements caused by exposure to hydrothermal fluids.